NEW DATA ON THE DENTAL CHARACTERISTICS EXHIBITED BY THE POPULATION OF THE KULAYKA CULTURE IN THE NOVOSIBIRSK OB AREA - M.S. Kishkurno (Вестник археологии, антропологии и этнографии, 2019)
The article covers the results of a study on the odontological series from the Kamenny Mys burial ground (3rd–2nd centuries BC). In this work, we set out to study the genesis of the Kulay population of the Early Iron Age in the Novosibirsk Ob area. The main relations of the population with the groups of adjacent territories, as well as the nature of their interaction with the local groups, were determined. The odontological series from the Kamenny Mys burial ground includes the teeth of 24 individuals: 12 males, 6 females and 10 adult individuals whose gender could not be determined. The anthropological materials were examined according to a standard procedure, which involves the description of the tooth crown morphology considering the archaic features of the dental morphology. Also, an intergroup comparative analysis was performed via the method of the principal component analysis using the program STATISTICA version 10.0. It was established that the dental characteristics exhibited by the Kulayka population reveal signs of mixed European-Mongoloid formation with a significant predominance of the Eastern component. We compared the morphological characteristics of the sample with data obtained for the populations of the Bronze Age and the Early Iron Age. The intergroup comparison revealed the closest connection between the Bolshaya Rechka culture and the Kulayka group. The studied material provides anthropological confirmation of the interaction between Kulayka (taiga) and Bolshaya Rechka traditions (steppe), drawing on the data about the burial rite and ceramic complexes. The comparison of the Kulayka series with Bronze Age samples suggests that the forest-steppe populations occupying the territories of the Novosibirsk and Tomsk Ob and the Ob-Irtysh areas had no effect on the genesis of the Kulayka population. We suppose that the origins of the Kulayka popula-tion in the Novosibirsk Ob area should be traced to the populations from the West Siberian taiga of the Bronze Age, which is significantly complicated by the lack of sufficiently complete and representative series dating back to the specified period from the territory of the Middle Ob area. Further accumulation of anthropological material from the Middle Ob area will provide the opportunity to trace the genesis of taiga populations of the Early Iron Age.